2017
DOI: 10.1044/2017_jslhr-l-16-0351
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical Morphology in Monolingual and Bilingual Children With and Without Language Impairment: The Case of Dutch Plurals and Past Participles

Abstract: https://doi.org/10.23641/asha.5165689.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 49 publications
2
22
0
2
Order By: Relevance
“…Effects of LI on vocabulary and morphology were large and remained stable over time, as expected (Rice, 2012). The effect of bilingualism on morphology also remained stable over time, likely due to a number of irregular items in our morphology task which have a low type frequency and are typically acquired at a late age (see, Boerma et al, 2017), but this effect was considerably smaller in magnitude than the effect of LI. Moreover, the difference in vocabulary size between the monolingual and bilingual children diminished over time, like in Farnia and Geva (2011).…”
Section: Discussionmentioning
confidence: 93%
“…Effects of LI on vocabulary and morphology were large and remained stable over time, as expected (Rice, 2012). The effect of bilingualism on morphology also remained stable over time, likely due to a number of irregular items in our morphology task which have a low type frequency and are typically acquired at a late age (see, Boerma et al, 2017), but this effect was considerably smaller in magnitude than the effect of LI. Moreover, the difference in vocabulary size between the monolingual and bilingual children diminished over time, like in Farnia and Geva (2011).…”
Section: Discussionmentioning
confidence: 93%
“…, Blom and Paradis ) and plural morphology (Boerma et al . ). In a study on the production of plural nouns and past participles in Dutch‐speaking monolingual and bilingual children with SLI tested when the children were between 4 and 7 years old (wave 1) and one year later (wave 2), Boerma et al .…”
Section: Introductionmentioning
confidence: 97%
“…Studies on children speaking Germanic languages such as English (Oetting and Rice ), Dutch (Boerma et al . ; Kuipers ), and German (Schöler and Kürsten ) have reported that plural formation is less problematic than tense, even though children with SLI have a depressed performance compared with their monolingual typically developing (mo‐TD) age‐matched peers. This contrasts with studies on Icelandic and Hungarian (Thordardottir , , Lukács et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations